Paradigms of endothelial stiffening in cardiovascular disease and vascular aging - Aguilar, Victor M.; Paul, Amit; Lazarko, Dana; Levitan, Irena (Frontiers in Physiology, 2023)
Endothelial cells, the inner lining of the blood vessels, are well-known to play a critical role in vascular function, while endothelial dysfunction due to different cardiovascular risk factors or accumulation of disruptive mechanisms that arise with aging lead to cardiovascular disease. In this review, we focus on endothelial stiffness, a fundamental biomechanical property that reflects cell resistance to deformation. In the first part of the review, we describe the mechanisms that determine endothelial stiffness, including RhoA-dependent contractile response, actin architecture and crosslinking, as well as the contributions of the intermediate filaments, vimentin and lamin. Then, we review the factors that induce endothelial stiffening, with the emphasis on mechanical signals, such as fluid shear stress, stretch and stiffness of the extracellular matrix, which are well-known to control endothelial biomechanics. We also describe in detail the contribution of lipid factors, particularly oxidized lipids, that were also shown to be crucial in regulation of endothelial stiffness. Furthermore, we discuss the relative contributions of these two mechanisms of endothelial stiffening in vasculature in cardiovascular disease and aging. Finally, we present the current state of knowledge about the role of endothelial stiffening in the disruption of endothelial cell-cell junctions that are responsible for the maintenance of the endothelial barrier.